2019
DOI: 10.1111/jrh.12375
|View full text |Cite
|
Sign up to set email alerts
|

Rural Clients’ Continuity Into Follow‐Up Substance Use Disorder Treatment: Impacts of Travel Time, Incentives, and Alerts

Abstract: Purpose Treatment after discharge from detoxification or residential treatment is associated with improved outcomes. We examined the influence of travel time on continuity into follow‐up treatment and whether financial incentives and weekly alerts have a modifying effect. Methods For a research intervention during October 2013 to December 2015, detoxification and residential substance use disorder treatment programs in Washington State were randomized into 4 groups: potential financial incentives for meeting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…But numerous barriers preclude access to MOUD in rural areas, the most significant of which is the lack of specialized providers able to prescribe MOUD ( 17 ). Rural OUD treatment seekers must often travel long distances and times— a burden that adds to the challenge of accessing and retaining individuals in care ( 12 , 18 , 19 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But numerous barriers preclude access to MOUD in rural areas, the most significant of which is the lack of specialized providers able to prescribe MOUD ( 17 ). Rural OUD treatment seekers must often travel long distances and times— a burden that adds to the challenge of accessing and retaining individuals in care ( 12 , 18 , 19 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…People who need to travel farther may have greater difficulty maintaining continuity of care due to the time burden and expenses of travel to physician visits. Travel distance has been shown to be an impediment to continuity of OUD care in prior studies, particularly in rural areas 37 . There are also area-level factors that may influence the relationship between access and quality, including more limited health and social services that support individuals seeking treatment for OUD.…”
Section: Discussionmentioning
confidence: 99%
“…to be an impediment to continuity of OUD care in prior studies, particularly in rural areas. 37 There are also area-level factors that may influence the relationship between access and quality, including more limited health and social services that support individuals seeking treatment for OUD. We found that most individuals with OUD lived relatively far from waivered physicians-a mean of about 7 miles in metro areas and 15 miles in non-metro areas.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic dependence is particularly important in light of evidence that proximity exerts a strong impact on treatment adherence and care continuity. Most care-seekers do not wish to travel far to receive care ( Garnick et al., 2020 ; Rosenbaum et al., 2011 ). Critical access MOUD units that service high local demand may face capacity constraints that likewise hinder treatment quality or timeliness ( Bouchery et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%